A Correlation Between Spiritual Level And Emotional Intelligence Toward Bullying In 12-15 Years Old Children At SMP Muhammadiyah 3 Purwokerto - Tohidin Saeful Aji; Dayat Trihadi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Background: Junior high school (SMP) children are the age of approaching adolescence who are still unstable and emotionally immature. They are close to their peers and tend to conflict with their parents which often affects their negative behavior such as bullying. Factors which affect bullying are spiritual level and emotional intelligence.Objective: This study aimed to determine the correlation between spiritual level of and emotional intelligence toward the propensity of bullying 12-15 years old children at SMP Muhammadiyah 3 Purwokerto.Method: This study was a quantitative descriptive with cross sectional method. The sample was children aged 12-15 years selected by proportional stratified random sampling technique from grades 7, 8, and 9 with the total of 178 children. This research instrument was a questionnaire and the finding was analyzed by the chi-square test.Results: The majority of children aged 12-15 years were female (51.7%), 14 years old (33.1%), grade 7 (41.6%), in a high spiritual level (65.2%), high emotional intelligence (55.1%), and tendency for moderate bullying behavior (51.1%). Chi-square test analysis from the spiritual level obtained p-value 0,000 <α = 0.05 and emotional intelligence scored p-value 0,000 <α = 0.05 toward the propensity of bullying.Conclusion: There is a correlation between the spiritual level and emotional intelligence toward the bullying tendency in 12-15 years old children at SMP Muhammadiyah 3 Purwokerto.